DESIGN OF ATS (AUTOMATIC TRANSFER SWITCH) SYSTEM BY INTEGRATING PLC (PROGRAMMABLE LOGIC CONTROLLER) AND INVERTER - MARCEAU A.F HAURISSA; MARSELIN JAMLAAY (CV KULTURA DIGITAL MEDIA, 2023)
Continuous and reliable electricity cannot be ensured to be available at all times. Therefore, to meet the needs of electrical energy continuity, backup or alternative sources of electrical energy are also utilized such as generators. Genset as a backup energy source will replace the function of PLN electricity which is the main energy source. Switching from PLN electricity to generators or vice versa requires equipment to regulate it known as ATS, but conventional ATS responds when there is a change in the electrical system usually has a generator starting time lag (up to 30 seconds). This is certainly detrimental to users who need a continuous source of electricity, such as shop cash registers. In this research, an ATS panel is built with the integration of PLC and inverter control. PLC will replace the limitations of relays and timers as controllers with simple wiring and programmable logic circuits as needed. The ATS system built is able to switch the inverter load in approximately less than 0.05 seconds when the PLN power source goes off and is able to run the generator on the first start to supply power to the main load as well as switching the inverter load to the main load supplied directly from the generator. So that lighting or other loads can be maintained in the order of a long time for the generator starting process or until the generator repair conditions if it fails to start.